Pengaruh Murottal Al-Quran Terhadap Penurunan Kecemasan Pada Lansia Penderita Hipertensi Di Puskesmas Paguyaman Pantai - Hasniati Hasniati; Yunita Suriani Suardi; Zendrawati Zendrawati; Harbaeni Harbaeni; Maria Kurniata Rante Kada (Jurnal Kesehatan Medika Udayana, 2022)
Background: Anxiety is one of the psychological factors that affect hypertension. Intense, excessive, and persistent worry and fear regarding everyday situations. The Purpose This study aims to determine the effect of Murottal Al-Qur'an on reducing anxiety in the elderly with hypertension at Paguyaman Pantai Health Center. Methods: This study was carried out for two weeks using a quasi-experimental method with a two group pre-posttest design approach, namely the measurement was carried out by giving initial observations before being given an intervention, after that an intervention was given, then a posttest or final observation was carried out. There are 20 samples who suffer from anxiety where 10 people in the intervention group murottal Al-Qur'an and 10 people in the control group without murottal Al-Qur'an. The instrument used was the Zung Self-Rating Anxiety Scale (SAS/SRAS) questionnaire. Analysis of the data in this study using Univariate Analysis and Bivariate Analysis. Bivariate analysis using Lambda Test Statistical Test. Results: The results showed that there were differences in the level of pre and post anxiety in the intervention group given Murottal Al-Qur'an, with a p-value of 0.001 or p?0.05, meaning there was a significant difference. Conclusion: The conclusion of this study is that there is an effect of murottal Al-Qur'an on reducing anxiety in the elderly with hypertension at the Paguyaman Beach Community Health Center.